The relationship of respiratory and cardiovascular hospital admissions to the southern California wildfires of 2003. Issue 3 (18th November 2008) - Delfino, R J; Brummel, S; Wu, J; Stern, H; Ostro, B; Lipsett, M; Winer, A; Street, D H; Zhang, L; Tjoa, T; Gillen, D L
Abstract : Objective: There is limited information on the public health impact of wildfires. The relationship of cardiorespiratory hospital admissions (n = 40 856) to wildfire-related particulate matter (PM2.5 ) during catastrophic wildfires in southern California in October 2003 was evaluated. Methods: Zip code level PM2.5 concentrations were estimated using spatial interpolations from measured PM2.5, light extinction, meteorological conditions, and smoke information from MODIS satellite images at 250 m resolution. Generalised estimating equations for Poisson data were used to assess the relationship between daily admissions and PM2.5, adjusted for weather, fungal spores (associated with asthma), weekend, zip code-level population and sociodemographics. Results: Associations of 2-day average PM2.5 with respiratory admissions were stronger during than before or after the fires. Average increases of 70 μg/m 3 PM2.5 during heavy smoke conditions compared with PM2.5 in the pre-wildfire period were associated with 34% increases in asthma admissions. The strongest wildfire-related PM2.5 associations were for people ages 65–99 years (10.1% increase per 10 μg/m 3 PM2.5, 95% CI 3.0% to 17.8%) and ages 0–4 years (8.3%, 95% CI 2.2% to 14.9%) followed by ages 20–64 years (4.1%, 95% CI −0.5% to 9.0%). There were no PM2.5 –asthma associations in children ages 5–18 years, although their admission rates significantly increased after the fires. Per 10 μg/m 3 wildfire-related PM2.5, acute bronchitis admissions across all ages increased by 9.6% (95% CI 1.8% to 17.9%), chronic obstructive pulmonary disease admissions for ages 20–64 years by 6.9% (95% CI 0.9% to 13.1%), and pneumonia admissions for ages 5–18 years by 6.4% (95% CI −1.0% to 14.2%). Acute bronchitis and pneumonia admissions also increased after the fires. There was limited evidence of a small impact of wildfire-related PM2.5 on cardiovascular admissions. Conclusions: Wildfire-related PM2.5 led to increased respiratory hospital admissions, especially asthma, suggesting that better preventive measures are required to reduce morbidity among vulnerable populations.